Bacterial and metabolic phenotypes associated with inadequate response to ursodeoxycholic acid treatment in primary biliary cholangitis - Laura Martinez‐Gili; Alexandros Pechlivanis; Julie A. K. McDonald; Sofina Begum; Jonathan Badrock; Jessica Dyson; Rebecca Jones; Gideon M. Hirschfield; Stephen Ryder; Richard Sandford; Simon Rushbrook; Douglas Thorburn; et al. (2023)
Primary biliary cholangitis (PBC) is a chronic cholestatic liver disease with ursodeoxycholic acid (UDCA) as first-line treatment. Poor response to UDCA is associated with a higher risk of progressing to cirrhosis, but the underlying mechanisms are unclear. UDCA modulates the composition of primary and bacterial-derived bile acids (BAs). We characterized the phenotypic response to UDCA based on BA and bacterial profiles of PBC patients treated with UDCA. Patients from the UK-PBC cohort (n = 419) treated with UDCA for a minimum of 12-months were assessed using the Barcelona dynamic response criteria. BAs from serum, urine, and feces were analyzed using Ultra-High-Performance Liquid Chromatography-Mass Spectrometry and fecal bacterial composition measured using 16S rRNA gene sequencing. We identified 191 non-responders, 212 responders, and a subgroup of responders with persistently elevated liver biomarkers (n = 16). Responders had higher fecal secondary and tertiary BAs than non-responders and lower urinary bile acid abundances, with the exception of 12-dehydrocholic acid, which was higher in responders. The sub-group of responders with poor liver function showed lower alpha-diversity evenness, lower abundance of fecal secondary and tertiary BAs than the other groups and lower levels of phyla with BA-deconjugation capacity (Actinobacteriota/Actinomycetota, Desulfobacterota, Verrucomicrobiota) compared to responders. UDCA dynamic response was associated with an increased capacity to generate oxo-/epimerized secondary BAs. 12-dehydrocholic acid is a potential biomarker of treatment response. Lower alpha-diversity and lower abundance of bacteria with BA deconjugation capacity might be associated with an incomplete response to treatment in some patients.